Making sense of Rome in the eighteenth century: walking and the French aesthetic imagination. Issue 3 (3rd July 2018) - Atkinson, Niall; Caviglia, Susanna
Abstract: This article traces the contours of a new way in which Rome was explored, imagined, and represented in the eighteenth century in texts and images by French travelers. These narratives, found in epistolary writings and the pictorial arts, reflected and suggested that viewers, readers, or strollers could enter into landscapes, wander through streetscapes, and commune with the past in both the space of the city and the space of representation. These narratives, found in epistolary writings and the pictorial arts, reflected and suggested that viewers, readers, or strollers could enter into landscapes, wander through streetscapes, and commune with the past in both the space of the city and the space of representation. French travelers brought with them a new modern form of walking linked to the creation of Parisian public boulevards, while contemporary philosophy associated the production of knowledge directly to the sensorial apparatus of the body. Writers would describe contemporary encounters with imagined figures from ancient history, while artists would visually reconfigure such encounters through the genre of the Roman capriccio . This pictorial mode was turned toward an exploration of the various ways in which movement, real or imagined, gave rise to popular forms of experiencing the Eternal City directly as well as to a verbal and visual language to express it to others. What this teaches us is that, for the enlightenment visitor, looking was not a passive act of consumption, but an active engagement with complex, confusing, and evocative material remains of the ancient city within the frame of the modern one.